The Effect of Mindmapping-Based Lecture Methods Assisted by Crossword Puzzles on Short Term Memory in View of Students' Visual Type Learning Styles in Class VII Civics Subjects at SMPN 1 Boyolangu - Hakim, Ikhwanul; Dirgantoro, Ajar (9 772338317006, 2023)
Abstract: The Effect of the Mindmapping-based Lecture Method assisted by Crosswords on Short Term Memory in terms of the Visual Type Learning Styles of students in Civics Class VII Subject at SMPN 1 Boyolangu. This research is motivated by the application of the lecture method by Civics teachers at SMPN 1 Boyolangu which is still conventional and does not really follow the development of students in the current era. As a result, students feel bored and bored because learning is less interesting and more varied. As a result, now students become less responsive and tend to choose silence without any desire to respond to every question asked by the teacher, besides that students also look quite difficult or unable to remember clearly if asked to convey their own ideas about what is being taught. The research method used is the Pre-Experimental Design type One Shot Case Study. The population in this study were 398 students. The sample used was 76 students from class VII A and B at SMPN 1 Boyolangu. Data collection uses tests and questionnaires while hypothesis testing goes through several stages such as instrument testing, prerequisite testing and data analysis. The results of the study were obtained if the mindmapping-based lecture method assisted by crossword puzzles on students' short term memory in terms of the visual learning styles of class VII students of SMPN 1 Boyolangu had an effect simultaneously or partially with positive significance. So that it can be concluded that if this method is applied in learning Civics subjects it will further encourage student enthusiasm in learning and be able to increase short term memory more sharply when absorbing information conveyed in the teacher's learning process of Civics subjects.